Effect of Dissolved Oxygen and Immersion Time on the Corrosion Behaviour of Mild Steel in Bicarbonate/Chloride Solution - Eyu, Gaius Debi (Materials (Basel), 2016)
The electrochemical behavior of mild steel in bicarbonate solution at different dissolved oxygen (DO) concentrations and immersion times has been studied under dynamic conditions using electrochemical techniques. The results show that both DO and immersion times influence the morphology of the corrosion products. In comparative tests, the corrosion rate was systematically found to be lower in solutions with lower DO, lower HCO(3)(−) concentrations and longer immersion time. The SEM analyses reveal that the iron dissolution rate was more severe in solutions containing higher DO. The decrease in corrosion rate can be attributed to the formation of a passive layer containing mainly [Formula: see text]-FeO (OH) and ([Formula: see text]-Fe(2)O(3)/Fe(3)O(4)) as confirmed by the X-ray diffractometry (XRD) and X-ray photoelectron spectroscopy (XPS). Passivation of mild steel is evident in electrochemical test at ≈ −600 mV(SCE) at pH [Formula: see text] 8 in dearated ([Formula: see text] 0.8 ppm DO) chloride bicarbonate solution under dynamic conditions.